PERAN KOMUNITAS HIJRAH DALAM MENUMBUHKAN KARAKTER ISLAMI GENERASI MILLENIAL DI MALANG - Didit Hendrawan Saputra; Chalimatus Sa’dijah; Syamsu Madyan (VICRATINA, 2020)
This nawak hijrah community is a place to facilitate the military generation who want to deepen Islamic religion with a relaxed implementation system that is not bound by regulations, so that the millennial generation is interested in following it. The focus of the research is related to the meaning of hijrah, efforts and solutions to the nawak hijrah community in growing the Islamic character of the millennial generation in Malang. Researchers used a qualitative approach to descriptive qualitative research. The data collection techniques using interviews, observation and documentation. In this role, this hawrah nawak community has an effort that is through Islamic studies, the nawak ngaji, football nawak which aims to foster the Islamic character of the millennial generation in Malang.